Norway rats reciprocate help according to the quality of help they received - Dolivo, Vassilissa (Biol Lett, 2015)
Direct reciprocity, according to the decision rule ‘help someone who has helped you before’, reflects cooperation based on the principle of postponed benefits. A predominant factor influencing Homo sapiens' motivation to reciprocate is an individual's perceived benefit resulting from the value of received help. But hitherto it has been unclear whether other species also base their decision to cooperate on the quality of received help. Previous experiments have demonstrated that Norway rats, Rattus norvegicus, cooperate using direct reciprocity decision rules in a variant of the iterated Prisoner's Dilemma, where they preferentially help cooperators instead of defectors. But, as the quality of obtained benefits has not been varied, it is yet unclear whether rats use the value of received help as decision criterion to pay help back. Here, we tested whether rats distinguish between different cooperators depending purely on the quality of their help. Our data show that a rat's propensity to reciprocate help is, indeed, adjusted to the perceived quality of the partner's previous help. When cooperating with two conspecific partners expending the same effort, rats apparently rely on obtained benefit to adjust their level of returned help.